A Soft Stretchable Sensor: Towards Peripheral Nerve Signal Sensing. (20th February 2018) - Hamilton, Charles; Tian, Kevin; Bae, Jinhye; Yang, Canhui; Alici, Gursel; Spinks, Geoffrey M.; Suo, Zhigang; Vlassak, Joost J.; Panhuis, Marc in het
ABSTRACT: We propose a 3D-printable soft, stretchable, and transparent hydrogel-elastomer device that is able to detect simulated 'nerve' signals. The signal is passed to a conductive hydrogel electrode through a non-contact method of capacitive coupling through polydimethylsiloxane (PDMS). We demonstrate that the device is able to detect sinusoidal waveforms passed through a simulated 'nerve' made from conductive hydrogel over a range of frequencies (1 kHz – 1 MHz). Analysis of signal detection showed a correlation to the electrode contact area and a Vin /Vout of larger than 10%. This provides the framework for the future development of a soft, 3D-printable, capacitive coupling device that can be used as a cuff electrode for detecting peripheral nerve signals.